Cooperation and Quality Assurance in Technical Translation Projects - Risku, Hanna (Language at Work - Bridging Theory and Practice, 2006)
The professional profile emerging to address today’s demands in business and industry bears little resemblance to the traditional view of translators as solitary all-rounders. Translators and technical writers are now increasingly seen as problem-solvers, working in teams and interacting with other experts. They act as text coordinators, language leads, localisers, information designers or content managers.